Mycoplasma hominis increases the risk for Ureaplasma parvum infection in Human immunodeficiency virus infected pregnant women - Nikita Nundlall; Bongekile Ngobese; Ravesh Singh; Partson Tinarwo; Nathlee Abbai (Journal of Infection in Developing Countries)
Introduction: Mycoplasma hominis and Ureaplasma parvum have been recently linked to sexually transmitted diseases and other conditions. There are a limited number of studies conducted on South African pregnant women that have assessed the prevalence and risk factors for genital mycoplasmas.